(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A key component in enhancing any company organization’s brand image is corporate social responsibility. This article primarily discusses the value of corporate social responsibility in enhancing an organization’s brand. Most scholarly and research studies rely on the past of corporate brand image, but they seldom ever examine the fundamentals of the process. The conceptual framework and hypothesis have been created upon the literature study. The hypothesis posits that the acceptance of CSR activities by an organization fosters employee believe in the organization, which in turn enhances the organization’s brand image.